2020
DOI: 10.1007/s00467-020-04759-1
|View full text |Cite
|
Sign up to set email alerts
|

2020 update on the renin–angiotensin–aldosterone system in pediatric kidney disease and its interactions with coronavirus

Abstract: The last decade was crucial for our understanding of the renin-angiotensin-aldosterone system (RAAS) as a two-axis, counterregulatory system, divided into the classical axis, formed by angiotensin-converting enzyme (ACE), angiotensin II (Ang II), and the angiotensin type 1 receptor (AT1R), and the alternative axis comprising angiotensin-converting enzyme 2 (ACE2), angiotensin-(1-7) (Ang-(1-7)), and the Mas receptor. Breakthrough discoveries also took place, with other RAAS endopeptides being described, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 141 publications
(279 reference statements)
0
13
0
Order By: Relevance
“…The reno-protective effects of ACE inhibitors and AT1R blockers in diabetic nephropathy and renal ischemia have suggested that the classical RAS axis is involved in the pathogenesis and progression of nephropathies [ 135 , 136 ]. On the other hand, several studies have shown that Ang 1–7, via Mas receptor activation, were reno-protective by counteracting AT1R-mediated Ang II renal damage [ 133 , 134 , 137 , 138 ]. It has been suggested that SARS-CoV-2 promoted both inhibition of ACE2 activity and lysosomal degradation of membrane-bound ACE2.…”
Section: Covid-19 and Acute Kidney Injury (Aki)mentioning
confidence: 99%
“…The reno-protective effects of ACE inhibitors and AT1R blockers in diabetic nephropathy and renal ischemia have suggested that the classical RAS axis is involved in the pathogenesis and progression of nephropathies [ 135 , 136 ]. On the other hand, several studies have shown that Ang 1–7, via Mas receptor activation, were reno-protective by counteracting AT1R-mediated Ang II renal damage [ 133 , 134 , 137 , 138 ]. It has been suggested that SARS-CoV-2 promoted both inhibition of ACE2 activity and lysosomal degradation of membrane-bound ACE2.…”
Section: Covid-19 and Acute Kidney Injury (Aki)mentioning
confidence: 99%
“…Ang-I has several ensuing fates that depend on the type of angiotensin converting enzymes present. This has been thoroughly reviewed by Silva et al in the paper discussing the interaction of RAAS with coronavirus ( 33 ). In the classical pathway, Ang-I is cleaved by angiotensin converting enzyme (ACE), a dicarboxypeptidase located on the surface of endothelial cells mainly in the pulmonary and intestinal capillaries ( 34 ), into an 8 amino acid peptide angiotensin II (Ang-II).…”
Section: Methodsmentioning
confidence: 99%
“…The reno-protective effects of ACE inhibitors and AT1R blockers in diabetic nephropathy and renal ischemia have suggested that the classical RAS axis is involved in the pathogenesis and progression of nephropathies [135,136]. On the other hand, several studies have shown that Ang 1-7, via Mas receptor activation, were reno-protective by counteracting AT1R-mediated Ang II renal damage [133,134,137,138]. It has been suggested that SARS-CoV-2 promoted both inhibition of ACE2 activity and lysosomal degradation of membrane-bound ACE2.…”
Section: Covid-19 and Acute Kidney Injury (Aki)mentioning
confidence: 99%